Addition of dacarbazine or cisplatin to interferon-α/interleukin-2 in metastatic melanoma: toxicity and immunological effects - Keilholz, Ulrich; Scheibenbogen, Carmen; Möhler, Thomas; Brossart, Peter; Maclachlan, David; Geueke, A.-M.; Jochim, Anita; Hunstein, Werner (Melanoma research, 1995)
The combination of chemotherapy and immunotherapy seems to improve response rate in metastatic melanoma. We investigated the effects on toxicity and immunological effects of a single dose of dacarbacin (DTIC; 850 mg/m2) or cisplatin (CDDP; 100 mg/m2) added to subsequent immunotherapy with interferon-a (IFN-α) and interleukin-2 (IL-2). Twelve patients, who did not respond to IFN-α/IL-2 alone were studied. Six received DTIC and IFN-α/IL-2, and six received CDDP and IFN-a/IL-2. DTIC did not add significant toxicity except for nausea. Significant thrombocytopenia was observed in two patients after CDDP. Although CDDP led to grade 3 nephrotoxicity in two patients, the IL-2-induced fluid retention was less severe than with IFN-α/IL-2 alone. Pharmacokinetics of IL-2 were not altered by DTIC, but higher IL-2 serum levels were found in patients with grade 3 nephrotoxicity after CDDP. The IL-2-related induction of secondary mediators (interferon-gamma, tumour necrosis factor-alpha, soluble CD25) was not impaired by chemotherapy and the induction of neopterin was significantly higher after addition of CDDP. One partial response was observed after addition of DTIC to IFN-α/IL-2, and one after addition of CDDP. The addition of a single dose of DTIC or CDDP to IFN-a/IL-2 is fairly well tolerated and does not abolish induction of secondary mediators. Randomized trials are necessary to test the clinical efficacy.